2019
DOI: 10.1097/md.0000000000014935
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of cognitive-behavioral intervention on anxiety and depression among social science education students

Abstract: Background: Anxiety is a common disorder which refers to a significant and persistent fear of one or more social or performance situations. This study investigated the impacts of cognitive-behavioral intervention on anxiety and depression among undergraduate students enrolled in social science education programs at public universities in the Southeast Nigeria. Methods: Participants were 55 undergraduate students enrolled in social science education programs at public un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 58 publications
5
34
1
Order By: Relevance
“…Also, in line with this study's findings, previous studies have reported the effectiveness of cognitive behavioral approaches in improving cognitive skills of different populations. [ 49 , 58 , 74 , 75 ] Similarly, earlier findings also showed that cognitive skill and behavioral disposition components influence critical thinking. [ 1 ] Exposing nursing students to critical thinking training gives an opportunity to utilize psychological assumptions in their professional practice.…”
Section: Discussionmentioning
confidence: 88%
“…Also, in line with this study's findings, previous studies have reported the effectiveness of cognitive behavioral approaches in improving cognitive skills of different populations. [ 49 , 58 , 74 , 75 ] Similarly, earlier findings also showed that cognitive skill and behavioral disposition components influence critical thinking. [ 1 ] Exposing nursing students to critical thinking training gives an opportunity to utilize psychological assumptions in their professional practice.…”
Section: Discussionmentioning
confidence: 88%
“…A clear example could be seen in the agreement between previous studies and the findings of the current study which justifies the worth of CBPT as the utmost technique for the treatment of children with diverse psychological and emotional disorder like traumatic disorder. [ 91 , 92 ] Consequently, the outcome of the study by Ezegbe et al [ 50 ] on randomized controlled evaluation of the effectiveness of music therapy on social anxiety symptoms validates the significant decrease in social anxiety disorder for the participants in intervention group at follow-up assessment after 3 months.…”
Section: Discussionmentioning
confidence: 94%
“…Their pulmonary functions were improved, the compliance of diagnosis and treatment and nursing was promoted and finally the QOL of the patients was significantly improved. Analysis of the causes shows that the correct cognition 14 of the patients on related diseases and treatment methods is improved by understanding their condition and nursing needs, working out the implementation plan of health education, issuing health manuals, broadcasting propaganda videos and holding health communication activities among patients and so on, in the implementation of nursing for the elderly patients with lung cancer. At the same time, a special psychological consultation platform was established to evaluate the psychological state of patients, to comfort and encourage patients by means of speech and physical contact, to help them obtain social and family support, so as to maintain a positive and stable psychological state; a good nurse–patient relationship was built during the nursing, so as to obtain the recognition and support of patients and their families, improve their diagnosis and treatment and nursing compliance 15 …”
Section: Discussionmentioning
confidence: 99%